A study on the number of demand among Non Muslim people towards family Takaful product / Nurulerna Suhani - Suhani, Nurulerna (2011)
Recently, demands on Family Takaful among non Muslim are increasing year by year in Malaysia. Due to that, this research was conduct to carry out the number of demand among non muslim people towards family takaful product. After conduct this research, the independent variable that influence the dependent variable which demand on family takaful product were income level, education level and population size. The objectives of this study were to identify the factors and the most factors that contribute to the number of demand among non muslim people towards family takaful product. The data set in this research study was collected from the Klang area which is 50 respondents become the sample in this research study by answer the questionnaire. The researcher use convenience sampling to obtain the data from the respondents. Other than that, the researcher also use SPSS to analyze the data obtain to get the results findings. The findings has show that three independent variable have significant relationship with demand among non muslim people towards family takaful product.